Balancing Rotor Dinamik Menggunakan Sinyal Suara - Saputra, Ariadi; Huda, Feblil; Akbar, Musthafa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rotating machines that have been operating within a certain period of time there is frequent vibration. The vibration is usually caused by unbalance, misalignment, bearing defect, and others. Unbalance is ranked as a first cause of vibration, which more than 80% cases of vibration caused by unbalance. This condition causes the balancing process needs to be done. A commonly method of vibration measurement uses vibration sensors such as accelerometer or vibrometer, that should be affixed to the machine in operation. This can cause discomfort and may even dangerous the operator when measuring the machines. The solution of the problem can be done using non contact measurement, where the sensor is not attached directly to the test equipment. Microphone is a device that can record the sound signal without necessarily contact the tested device. The unbalance tendency of the test is characterized by the presence of the dominant frequency at one rotational speed (1 x rpm). From the test, the result of balancing of normal condition on one rotor and two rotors are 0.039 V and 0.031 V with balancing efficiency 87.88% and 80.74% respectively. The addition of unbalance mass on one rotor and two rotors is obtained balancing result of 0.031 V and 5.88x10-3 V with efficiency balancing of 93.58% and 97.43% respectively.Keywords : voice signal, unbalance, balancing, microphone, unbalance mass